REMASTERING SISTEM OPERASI BERBASIS LINUX UNTUK ADMINISTRATOR JARINGAN - Ilyas, Alhafidh (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
The study was motivated by the problem of how a user is able to take advantage of the free Linux operatingsystem software, as well as to develop it into a new Linux distribution for both network administrators andcreate documentation in the form of user manuals or instructions for use to assist the operation of Linuxdistributions that have been developed. The aim of this study is to develop a Linux operating system thatalready exists into a new Linux distribution for network administrators, as well as a medium of learningscience in the campus computer network Ubudiyah University of Indonesia. This study used a qualitativeresearch method, where the researcher is a key instrument, data collection techniques performed bytriangulation or combined, data analysis is inductive or qualitative research results further emphasize andgeneralize. The results of the research remastering Linux-based operating system for networkadministrators, the creation of a new linux distribution that is devoted to the administrator and learningcomputer science network and is able to improve the performance of Linux users, although still notmaximized. Linux is a free operating system to be developed without having to worry about licensing as wellas on the author, create a new linux distribution from an existing distribution methods remastering with theaim of developing a linux distro specifically for network administrators and instructional media computerscience network within the campus of the University Ubudiyah Indonesia. The limiting factor in this study isthe limited capacity of the ability of researchers, so the future is expected for the further development of thisresearch.Keyword : Remastering, Linux, Network Administrator, System Operation